The Comparison of Students Achievement by the College Entrance Lane at the Teachers Training and Education Faculty of Syiah Kuala University - Amiruddin Amiruddin; Zulfadhli Zulfadhli; Asmaul Husna (Journal of Education and Learning (EduLearn), 2018)
The study aims to determine differences in the achievement of students who pass the National Selection of State Universities (SNMPTN), the Selection of Joint Entrance State University (SBMPTN), and the Joint Entrance examination (UMB) at the Faculty of Teachers Training and Education (FKIP) at the University of Syiah Kuala. The study used descriptive method with a quantitative approach. The population in this study were all FKIP Unsyiah students entering university in 2013 that passed the SNMPTN, SBMPTN, and UMB. The population pool was as many as 1,038 students with 289 students selected for the sample using the Proportionate Stratified Random Sampling technique. The One Way Anova Test was used for data analysis followed by a Least Significance Difference (LSD) test. Hypothesis in this research is there are differences in the achievement of FKIP Unsyiah students passed through SNMPTN, SBMPTN, and UMB. The results showed that the achievement of FKIP Unsyiah students who passed through the SBMPTN had average GPAs of 3.46, 3.32 for the SNMPTN and 3.36 for the UMB. Based on the results, it can be concluded that students who pass the SBMPTN had greater achievement than student who pass the SNMPTN and UMB.